CATCH PERFORMANCE OF PURSE SEINE CASE STUDY ON KMN DIVA BAHARI AT KENDARI FISHING PORT - Khikmawati, Liya Tri; Setyawan Sayuti, Noar Mudda; Rizal, Ahsanul; Hutapea, Roma Yuli F (Politeknik Kelautan dan Perikanan Dumai, 2024)
Purse seines are a type of fishing gear that operates by surrounding schools of fish. The target fish caught from purse seines themselves are small pelagic fish that are in schools. One of the areas where the majority of fishermen use purse seines is PPS Kendari, where the target fish caught are scallops, skipjack tuna and tuna. The price of self-caught fish is influenced by the type, size and quality of the fish itself. One of the reasons for the feasibility of a fishing business can be assessed from the opinions obtained from the business carried out. Having data related to the performance of catches from a fishing business will provide an initial picture regarding the feasibility of the fishing business. Data collection was carried out by participating in KMN Diva Bahari fishing activities made 8 fishing trips (1 trip 5-8 days). Then fish samples are taken for each fishing operation and the type, number and size are seen/measured. The data that has been collected is then presented in tables and figures and then compared with literature studies regarding the size of fish worth catching. Based on data obtained in the field, it was found that the fish caught were gliding (the majority), tuna, mackerel, sunglir, baby yellowfin tuna and skipjack. Where all the tuna, skipjack, sunglir, tuna fish that were caught were not yet worth catching. Meanwhile, for mackerel, blue kites are included in the fish size category worth catching. Several things that influence the size of fish caught that are not suitable are catching in FAD areas where one of the functions of FADs is a place for spawning and rearing, fishing seasons and fish areas.